Pengaruh status nutrisi terhadap kualitas hidup pada pasien hemodialisis - Putri, Zahira Sukma Yulia; Fikri, Zahid; Setyowati, Lilis; Sunardi, Sunardi (Holistik Jurnal Kesehatan, 2025)
Background: The quality of life of patients with HD is often affected by physical and psychological conditions, which are influenced by various factors, including nutritional status. Decreased nutritional status in HD patients can have a significant impact on their quality of life. However, the influence of nutritional status on quality of life in HD patients in Indonesia has not been widely explored. Purpose: To analyze the effect of nutritional status on quality of life in hemodialysis patients Method: This study was an observational study with a cross-sectional approach involving 184 HD patients who met the inclusion criteria, namely patients who had undergone HD for ≥ 6 months. Nutritional status was measured using the Dialysis Malnutrition Score (DMS), while quality of life was measured using the Kidney Disease Quality of Life-36 (KDQOL-36). Data were analyzed using simple linear regression with the IBM SPSS version 27 application with a significance level (p-value <0.05). Results: The results showed that the average respondent had good nutritional status (83.0%), while the rest had mild malnutrition (16.30%) and severe malnutrition (0.50%). For the level of quality of life, the average respondent has a good quality of life (54.9%), while the rest of the quality of life is very good (40.8%) and moderate (4.3%). Statistical tests showed a significant relationship between nutritional status and quality of life with (p-value 0.001), with a negative relationship direction and a strong coefficient level. Conclusion: This study confirms that nutritional status has a significant influence on quality of life in HD patients.   Keywords: Hemodialysis; Quality of Life; Nutritional Status.   Pendahuluan:Kualitas hidup pasien hemodialisis (HD) sering kali terpengaruh oleh kondisi fisik dan psikologis, yang dipengaruhi oleh berbagai faktor, termasuk status nutrisi. Penurunan status gizi pada pasien HD dapat berdampak signifikan pada kualitas hidup mereka. Namun, pengaruh status nutrisi terhadap kualitas hidup pada pasien HD di Indonesia belum banyak dieksplorasi. Tujuan:Untuk menganalisis pengaruh status nutrisi terhadap kualitas hidup pada pasien hemodialisis. Metode: Penelitian studi observasional dengan pendekatan cross-sectional yang melibatkan 184 pasien HD yang memenuhi kriteria inklusi, yaitu pasien yang telah menjalani HD selama ≥ 6 bulan. Status nutrisi diukur menggunakan Dialysis Malnutrition Score (DMS), sedangkan kualitas hidup diukur dengan Kidney Disease Quality of Life-36 (KDQOL-36). Data dianalisis menggunakan regresi linier sederhana dengan aplikasi IBM SPSS versi 27 dengan tingkat signifikansi (p-value <0.05). Hasil: Responden rata-rata memiliki status gizi baik (83.0%), sedangkan sisanya mengalami malnutrisi ringan (16.30%) dan malnutrisi berat (0.50%). Untuk tingkat kualitas hidup rata-rata responden memiliki kualitas hidup baik (54.9%), sedangkan sisanya kualitas hidup sangat baik (40.8%) dan sedang (4.3%). Uji statistik menunjukkan adanya hubungan signifikan antara status nutrisi terhadap kualitas hidup dengan p-value 0.001 dan arah hubungan yang negatif serta tingkat koefisien yang tergolong kuat. Simpulan: Status nutrisi memiliki pengaruh signifikan terhadap kualitas hidup pada pasien HD.   Kata Kunci: Hemodialisis; Kualitas Hidup; Status Nutrisi.